Aplicação do método Jack-Knife para determinar falhas críticas em uma mandrilhadora - Marcovicz, Fabio Luiz (2018)
The determination of failures that most compromise the maintenance performance in a company assets is not easy to identify. Therefore, it is proposed to study and apply the method of prioritizing failures Jack-Knife in a boring machine. The method consists of the construction of a diagram, which the faults are located in four quadrants. To get the diagram you need to have a reliable database of the history and actions that performed maintenance on an equipment or system. To identify which failures were critical and which contributed most to the unavailability. The method also allows the analysis of two parameters, which are related at the same time, on the same diagram which comes from the number of failures and the time of repair of each failure. This information is expressed in a scatter plot, in which the axes are in logarithmic scale. And the limits are applied to separate the quadrants. The faults that are located in the upper right quadrant are the critical failures that have had the longer repair time and the higher frequency of occurrence. These are the first to receive improvement actions so that they can be resolved and not be repeated again. Two critical failures were found in a boring machine. They are the broken belt and failures of the hydraulic system. These two failures together account for half of the equipment downtime. These failed systems are covered by preventive plans and these plans have to be referenced with the scheduled hours of use of the equipment and not for time or days running.